Seroprevalence of SARS-CoV-2 antibodies in the general population of Oman: results from four successive nationwide sero-epidemiological surveys. (November 2021) - Al-Abri, Seif Salem; Al-Wahaibi, Adil; Al-Kindi, Hanan; Kurup, Padmamohan J; Al-Maqbali, Ali; Al-Mayahi, Zayid; Al-Tobi, Mohammed Hamed; Al-Katheri, Salim Habbash; Albusaidi, Sultan; Al-Sukaiti, Mahmood Humaid; Al Balushi, Ahmed Yar Mohammed; Abdelgadir, Iyad Omer; et al.
Highlights: The seroprevalence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in Oman has increased from 5.5% to 22%. A difference in seroprevalence was found between genders. The risk of getting COVID-19 was 96% higher in close contacts of patients with coronavirus disease 2019 (COVID-19). SARS-CoV-2 dissemination varied by governorate in Oman. COVID-19 was higher in non-Omanis compared with Omanis prior to the introduction of health measures. ABSTRACT: Objective: To assess the seroprevalence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in Oman and longitudinal changes in antibody levels over time within the first 11 months of the coronavirus disease 2019 (COVID-19) pandemic. Methods: This nationwide cross-sectional study was conducted as a four-cycle serosurvey using a multi-stage stratified sampling method from July to November 2020. A questionnaire was used and included demographics, history of acute respiratory infection and list of symptoms, COVID-19 contact, previous diagnosis or admission, travel history and risk factors. Results: In total, 17, 457 participants were surveyed. Thirty percent were female and 66.3% were Omani. There was a significant increase in seroprevalence throughout the study cycles, from 5.5% (4.8–6.2%) in Cycle 1 to 22% (19.6–24.6%) in Cycle 4. There was no difference in seroprevalence between genders, but significant differences were found between age groups. There was a transition of seroprevalence from being higher in non-Omanis than Omanis in Cycle 1 [9.1% (7.6–10.9%) vs 3.2% (2.6–3.9%)] to being higher in Omanis than non-Omanis in Cycle 4 [24.3% (21.0–27.9%) vs 16.8% (14.9–18.9%)]. There was remarkable variation in the seroprevalence of SARS-CoV-2 according to governorate. Close contacts of people with COVID-19 had a 96% higher risk of having the disease [adjusted odds ratio (AOR) 1.96, 95% confidence intervals (CI) 1.64–2.34]. Labourers had 58% higher risk of infection compared with office workers (AOR 1.58, 95% CI 1.04–2.35). Conclusion: This study showed a wide variation in the spread of SARS-CoV-2 across governorates in Oman, with higher estimated seroprevalence in migrants in the first two cycles. Prevalence estimates remain low and are insufficient to provide herd immunity.